2001
DOI: 10.1590/s1519-566x2001000200013
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de genótipos de caupi Vigna unguiculata (L.) Walp. resistentes a Callosobruchus maculatus (Fabr.) (Coleoptera: Bruchidae)

Abstract: -The present work aimed to identify sources of resistance in 30 cowpea genotypes, from EMBRAPA Meio-Norte, to the cowpea weevil Callosobruchus maculatus (Fabr.). In a no choice test, two pairs of the insect were confined in 30 grains of each genotype, in a completely randomized design with five replications. To evaluate the resistance of the genotypes, the parameters: number of eggs/ female, viability of eggs, duration and viability of the immature phase, natural rate of population increase, and resistance ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
(11 reference statements)
1
7
0
5
Order By: Relevance
“…Os grãos foram acomodados em sacos plásticos a uma temperatura de -5°C (em freezer) durante 30 dias, com a finalidade de eliminar infestações latentes (LIMA et al, 2001).…”
Section: Methodsunclassified
“…Os grãos foram acomodados em sacos plásticos a uma temperatura de -5°C (em freezer) durante 30 dias, com a finalidade de eliminar infestações latentes (LIMA et al, 2001).…”
Section: Methodsunclassified
“…Lima et al (2001) identifying cowpea genotypes resistant to Callosobruchus maculatus (F.), observed that morphological causes and tegument texture affect the preference for oviposition. Nwanze et al (1975) observed higher oviposition of C. maculatus on smooth grain than rough grain.…”
Section: First Selection Of Genotypesmentioning
confidence: 99%
“…Mar. 2019 report that C. maculatus insects prefer seeds with soft and smooth integument for oviposition, in relation to the harsh and rough homologues, as ratified byLima et al (2001) in their studies with C. maculatus. ).…”
mentioning
confidence: 93%
“…Among the main crop pests, the cowpea weevil Callosobruchus maculatus (Fabr.) holds an elevated harmful potential, especially during the storage, generating qualitative and quantitative losses (Lima et al, 2001) The infestations by C. maculatus may begin in the field, were the females lay eggs in the surface of grains or seeds (Marsaro Júnior & Vilarinho, 2011). The larvae of this bruchid, when hatching, penetrate the grains and feed on the internal content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation